2006
DOI: 10.1007/s10350-006-0748-2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Polyps: A Cause of Late Bleeding in Stapled Hemorrhoidectomy

Abstract: Bleeding from inflammatory polyps occurs in a significant number of patients undergoing stapled hemorrhoidectomy. Mild bleeding several weeks or months after the procedure should prompt a search for inflammatory polyps at the staple line. Simple excision of the polyps was adequate treatment and has not resulted in rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
0
18
1
1
Order By: Relevance
“…3,[17][18][19][20] Early thrombosed external hemorrhoids (TEH) were also reported, with the overall early occurrence rate ranging from 0 to 13% and a median occurrence of 4.51%. 21 Overall rates of urinary retention ranged from 0 to 22%.…”
Section: -16 Documented Complications Of Hemorrhoidopexy Porrettmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[17][18][19][20] Early thrombosed external hemorrhoids (TEH) were also reported, with the overall early occurrence rate ranging from 0 to 13% and a median occurrence of 4.51%. 21 Overall rates of urinary retention ranged from 0 to 22%.…”
Section: -16 Documented Complications Of Hemorrhoidopexy Porrettmentioning
confidence: 99%
“…23 Submucosal anastomotic cysts were reported. 17,25 Recurrence of hemorrhoids following the procedure occurred up to 58.9% of patients. 32 …”
Section: -16 Documented Complications Of Hemorrhoidopexy Porrettmentioning
confidence: 99%
“…Published recurrence rates range up to 25.9% [28], and published reoperation rates for recurrence range up to 14.7% [39]. In general, performing minor concomitant procedures has no negative effect on postoperative reconvalescence, complication or reoperation rates and is generally not regarded as contraindicated [7,[40][41][42].…”
Section: Discussionmentioning
confidence: 97%
“…Fondran et al recommended for late bleeding, which the patient may attribute to recurrence of hemorrhoids, prompt anoscopic examination for granulation polyps. The authors suggested that if these granulomas were found, they could be adequately treated with simple polypectomy [34].…”
Section: Hemorrhagementioning
confidence: 99%